(untitled) (Journal of Educational Sciences, 2017)
The article describes the basics of teaching effective use of multimedia presentations at training professional Russian language. We consider the inclusion of the requirement of multimedia presentations in the practical exercises. Multimedia support sessions via audio-visual illustrations dramatically optimizes the learning process. The authors analyze and summarize the lighting design of multimedia presentations in the linguistic, educational and methodical literature in the context of modern requirements,result-oriented. It is noted that the extra-linguistic components of the text in the specialty with the presentation actualize not only auditory, and audiovisual reception, which does not focus on a single source of information, and distributed between verbal perception of the teacher of speech, visual perception of his non-verbal behavior and visual perception slides.